1997
DOI: 10.1023/a:1005729304068
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal node-negative breast cancer: May adjuvant chemotherapy be indicated by the analysis of nuclear DNA dynamics?

Abstract: The management of premenopausal node-negative breast cancer patients is discussed controversially. Accurate cellular as well as biochemical markers are essential for this cancer group to identify high risk patients needing adjuvant chemotherapy. In the present study, flow cytometric DNA analysis (DNA-ploidy status, DNA-index, S-phase fraction, S+(G2+M)-phase fraction) and clinico-pathological variables (clinical stage, tumor size, receptor status, age, histological type and grade) as prognostic factors were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…From eight [ 7 , 9 11 , 16 , 22 , 26 , 33 ] studies using 50 years of age as a cut point, the RR of patients with aneuploidy tumor less than 50 years compared to those above 50 years old was 1.00 (95% CI, 0.91 to 1.11; P = 0.94; Figure 3H ). Likewise, pooled analysis of the studies [ 20 , 26 , 34 ] using 40 years as a cut point showed a similar result (RR = 0.99; 95% CI, 0.81 to 1.21; P = 0.92). Four studies [ 7 , 17 , 18 , 34 ] explored the aneuploidy frequency in premenopausal and postmenopausal women with BCs and our analysis demonstrated that aneuploidy was not significantly associated with menopausal status (RR = 1.02; 95% CI, 0.93 to 1.12; P = 0.66; sign test: P = 0.04).…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…From eight [ 7 , 9 11 , 16 , 22 , 26 , 33 ] studies using 50 years of age as a cut point, the RR of patients with aneuploidy tumor less than 50 years compared to those above 50 years old was 1.00 (95% CI, 0.91 to 1.11; P = 0.94; Figure 3H ). Likewise, pooled analysis of the studies [ 20 , 26 , 34 ] using 40 years as a cut point showed a similar result (RR = 0.99; 95% CI, 0.81 to 1.21; P = 0.92). Four studies [ 7 , 17 , 18 , 34 ] explored the aneuploidy frequency in premenopausal and postmenopausal women with BCs and our analysis demonstrated that aneuploidy was not significantly associated with menopausal status (RR = 1.02; 95% CI, 0.93 to 1.12; P = 0.66; sign test: P = 0.04).…”
Section: Resultsmentioning
confidence: 58%
“…Six studies [ 7 , 11 , 20 , 25 , 34 , 35 ] investigated the correlation between aneuploidy rate and tumor pTNM stages. This pooled analysis revealed that aneuploidy was significantly less frequent in patients with stage I BC compared to those with stages II-IV tumors (RR = 0.84; 95% CI, 0.74 to 0.96; P = 0.01, random-effects model; Figure 3A ; sign test: P = 1; RD = −0.12; 95% CI, −0.17 to −0.08; P < 0.00001, fixed- effect model).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, grade I and grade II are designated low grade (non-high grade), and grade III is considered to be high grade. 9,10) For grading of DCIS, the Van Nuys DCIS classification 11,12) was used. In this study, group 3 was designated as high grade, and the other two groups were designated as low grade (non-high grade).…”
Section: Methodsmentioning
confidence: 99%